Neuropeptide Bursicon Influences Reproductive Physiology in Tribolium Castaneum - Li, Jingjing; Zhu, Zidan; Bi, Jingxiu; Feng, Qili; Beerntsen, Brenda T.; Song, Qisheng (Frontiers in Physiology, 2021)
Bursicon is a neuropeptide belonging to the cystine knot family and is composed of burs and partner of burs (pburs) subunits. It can form heterodimers or homodimers to execute different biological functions. Bursicon heterodimers regulate cuticle sclerotization and wing maturation, whereas bursicon homodimers mediate innate immunity and midgut stem cell proliferation. A recent study has shown that bursicon potentially induces the expression of vitellogenin (Vg) in the black tiger shrimp Penaeus monodon; however, the underlying mechanism remains unknown. In this study, we investigated the role of bursicon in the reproductive physiology of the red flour beetle, Tribolium castaneum. The knockdown of burs, pburs, or its receptor T. castaneum rickets (Tcrk) in 2-day pupae significantly downregulated the expression levels of Vg1, Vg2, and Vg receptor (VgR) genes in females 3- and 5-day post-adult emergence, leading to abnormal oocytes with limited Vg content. The silencing of burs repressed the number of eggs laid and completely inhibited egg hatch, whereas the silencing of pburs dramatically decreased the number of eggs laid, hatch rate, and offspring larval size, and this RNA interference (RNAi) effects persisted to the next generation. Furthermore, the knockdown of burs or pburs downregulated the expression of the insulin/insulin-like signaling/target of rapamycin (TOR) signaling genes encoding insulin receptor (InR), protein kinase B (Akt), TOR, and ribosomal protein S6 kinase (S6K). Most importantly, the injection of recombinant pburs (r-pburs) protein was able to upregulate the expression of Vg, VgR, InR, Akt, TOR, S6K, JH synthesis (JHAMT), Methoprene-tolerant (Met), and Taiman (Tai) in normal females and rescue the expression of Vg and VgR in pburs RNAi females but failed to rescue Vg and VgR in Tcrk knockdown females. We infer that bursicon homodimers influence Vg expression via the receptor Tcrk, possibly by mediating the expression of the juvenile hormone (JH) and IIS/TOR pathway genes, thereby regulating reproduction in T. castaneum.